Variabilidad de la Frecuencia Cardíaca Materna en Decúbito Supino y Lateral Durante el Embarazo a Término - González Camarena, R.; Carrasco Sosa, S.; Gaitán González, J. M.; Pimentel Aguilar, A. B.; Rodríguez Vera, R. N.; Vargas García, C. (Revista Mexicana de Ingenieria Biomedica, 1999)
It is well known that the patterns of fetal heart rate variability are affected during the maternal supine position due to aortocaval compression; however, the corresponding maternal effects have been unexplored. The purpose of the present study was to determine, by lineal and non-lineal techniques, whether or not the supine position alters the maternal heart rate variability. Hence, we compare the heart rate variability response during the supine and the left lateral position in 19 women with normal pregnancy at term. Respiration and electrocardiogram were acquired at a sample frequency of 1,000 Hz (5 minutes length) and processed to get parameters of RR intervals by temporal, spectral, return maps and Tone-Entropy analyses. Statistical comparison between positions indicated non-significant (p>0.05) differences in the computed temporal parameters. Spectral (total power, low-frequency power, high-frequency power and low over high ratio) and non-lineal parameters were also non-significant. Our results suggest that nevertheless the expected hemodynamic changes, the autonomic nervous system response of the pregnant women at term is not altered by the supine position. However, this conclusion is made cautiously, since the non-stationarity of the signal produced analysis limitations.